Implementasi Program Pengabdian Masyarakat Untuk Branding Dan Digitalisasi UMKM Di Desa Jayamukti Kab. Bekasi - Pupung Purnamasari; Randa Septi Harmona; Rifa Mu’minatul Kirom; Regia Nurul Aini (CV. ITTC INDONESIA, 2024)
The community service program in Jayamukti Village was motivated by the low understanding of MSMEs regarding branding and digitalization, which affects their competitiveness in the market. The program aimed to enhance the visibility and operational efficiency of MSMEs through the implementation of branding and digitalization strategies. The methods used included door-to-door outreach, training in banner creation as a promotional tool, QRIS implementation for digital transactions, and registering business locations on Google Maps to improve consumer accessibility. The results showed that the program successfully increased the attractiveness and accessibility of MSMEs and facilitated cashless transactions, despite some challenges such as resistance to new technology and verification issues in the QRIS implementation process. Overall, the program had a positive impact on MSMEs in Jayamukti Village by improving their readiness to compete in the digital era. In the future, program development can focus on more intensive digital education and technological capacity building to address the challenges faced and ensure the sustainability of the program's impact.